2008
DOI: 10.1016/j.molonc.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale genomic analysis of ovarian carcinomas

Abstract: Epithelial ovarian cancers are typified by frequent genomic aberrations that have been difficult to unravel. Recently, high‐resolution array technologies have provided the first glimpse of the remarkable complexity of these aberrations with some ovarian cancers containing hundreds of copy number breakpoints, micro‐deletions and amplifications. Many of these alterations contain cancer‐related genes suggesting that the majority is disease‐associated and not just the product of random genomic instability. Future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…Serous ovarian tumors are known to have highly rearranged genomes and chromosomal instability 33,34 . Illumina SNP arrays confirmed that ~190 chromosomal aberrations and loss-of-heterozygosity regions were present in this tumor We first performed tumor-normal comparisons and assessed whether step-wise application of the filters to both genomes affected the number of discordant variants (Supplementary Note 8).…”
Section: Somatic Mutations In Ovarian Tumor Genomesmentioning
confidence: 99%
“…Serous ovarian tumors are known to have highly rearranged genomes and chromosomal instability 33,34 . Illumina SNP arrays confirmed that ~190 chromosomal aberrations and loss-of-heterozygosity regions were present in this tumor We first performed tumor-normal comparisons and assessed whether step-wise application of the filters to both genomes affected the number of discordant variants (Supplementary Note 8).…”
Section: Somatic Mutations In Ovarian Tumor Genomesmentioning
confidence: 99%
“…Activation of Akt is observed in up to 70% of ovarian cancers (4) due to a variety of causes, including PIK3CA mutations (8%-12%) or amplification (3%-8%) and/or PTEN loss (27%) or mutations (3-8%) (1,(5)(6)(7)(8)(9)(10). Loss of Pten (11,12) or overexpression of activated PI3K in the mouse ovarian surface epithelium (OSE) (13) do not lead to tumor formation; however, the ability of mutant Pik3ca to initiate tumorigenesis or drive tumor progression has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cytogenetic studies support the observation that chromosome 19 is typically involved in both clonal and nonclonal numerical and structural aberrations (8,31 ), and that the vast majority of OCas are polyploid (8,10,11,32 ). Therefore, the averaging algorithms of aCGH used in studies resulting in the frequent loss of the locus (33,34 ) failed to take into account ploidy and copy number heterogeneity (12 ). FISH showed 2 copies of the KLK locus at the normal mapping location (19q13.3/4).…”
Section: Discussionmentioning
confidence: 73%